Impact of banking deregulation on bank efficiency and productivity growth: Evidence from Indonesia - Defung, Felisitas (Curtin University, 2014)
This thesis investigates the impact of regulatory changes during the restructuring periods on bank efficiency and productivity growth in Indonesia. The bootstrap of non-parametric method and censored regression techniques are used to obtain the outcome. A significant effect of regulatory change on revenue-based efficiency is observed. In addition, technological change is found to be the major driver of productivity growth. Therefore, regulatory changes should continue to realise the potential of the Indonesian banking sector.